ESL WRITING VARIABILITY: WRITING TASKS, GENDER AND PROFICIENCY LEVEL - Sabariah M. D. Rashid; Shameem Rafik-Galea (Universitas Katolik Indonesia Atma Jaya, 2007)
Research focusing on L1 (native speakers of English) writers has shown that students tend to perform differently on different writing tasks. L1 students perform better on narrative and descriptive writing tasks than argumentative. In fact, some scholars have suggested that L1 students lack a schema for argumentative writing, which perhaps contribute to their poor performance on argumentative writing tasks. This tendency seems also applicable to L2 (non-native speakers of English) writers. This paper reports the findings of a study on the impact of narrative and argumentative writing tasks, gender and proficiency level on the quality of Malaysian English as a second language (ESL) learners’ writing. The findings of this study are discussed in the light of variability in ESL writing. Their implications for writing assessment practices are also highlighted. Keywords: ESL writing, task variability, gender, proficiencylevel